DIFFERENCES IN LEUKOCYTE RATE BETWEEN ACUTE NONPERFORATED AND PERFORATED APPENDICITIS IN HOSPITALISED PATIENTS BANDAR LAMPUNG-INDONESIA - Festy Ladyani; Nur Fitria Dewi (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Acute appendicitis is one of the most common acute abdominal pain. A late check up and diagnosis could bring harms which is turning into perforated appendicitis. Leukocyte count is a laboratory collation that is generous and quick to diagnose the acute apendicitis and perforated appendicitis, however there’s no certain limit of the leukocytes count to recognize whether it is acute apendicitis or perforated appendicitis.Purpose: This research was to find out the comparison of leucocyte count average between acute appendicitis and perforation appendicitis in Dr. H. Abdul Moeleok public hospital of Lampung province in 2014-2016.Methods: An analytic research with cross sectional approach. Population was 382 patients with appendicitis in Dr. Hi. Abdul Moeloek public hospital. Samples were taken using total sampling technique with 196 respondent samples for acute appendicitis and 196 respondent samples for perforation appendicitis. Data were analyzed by using univariate analysis with percentage and bivariate analysis with t-test.Results: the average of leucocyte count of acute appendicitis patients was 10,907 with minimum and maximum leucocyte count of 5,000 and 18,500 respectively. The average of leucocyte count of perforation appendicitis patients was 22,789 with minimum and maximum leucocyte count of 16,500 and 31,000 respectively. There were differences of leucocyte counts between acute appendicitis patients and perforation appendicitis patients with p-value < 0.05.Conclusion: there were significant differences of leucocyte count averages between acute appendicitis and perforation appendicitis.